VALIDAÇÃO DE ÁLBUM SERIADO PARA ENFERMEIROS DA ATENÇÃO BÁSICA SOBRE VIOLÊNCIA DOMÉSTICA CONTRA A MULHER - Viviane Maria de Pádua Rios Magalhães; Rosimeire Ferreira dos Santos; Carmen Viana Ramos; Lucíola Galvão Gondim Corrêa Feitosa; Eliana Campêlo Lago; Elayne Kelly Sepedro Sousa; Camila Aparecida Pinheiro Landim Almeida (Universidade Federal do Paraná, 2020)
Objective: to validate the content and appearance of a serial album on domestic violence against women for primary care nurses. Method: a methodological study, of appearance and content validation, developed in Teresina, Piauí, Brazil, in 2018. The data were collected by sending the evaluation instruments via e-mail to selected specialists on the Lattes Platform. In the analysis, the Content Validity Index was used with an established value of 0.78. Results: 15 specialists participated, with experience in educational technologies and/or violence against women, most of them have doctorates and nursing degrees. Regarding structure and presentation, objectives and relevance, all items were considered validated by experts. The global Content Validity Index of the educational technology was 0.93. Conclusion: The serial album has been validated for content and appearance, suggesting that this educational technology enables health education actions performed by nurses of Basic Care.